167k views
1 vote
4 + (5² - 2³)Complete the following questions

User Cepatt
by
5.4k points

1 Answer

7 votes

Step 1: Concept

Use the order of operations below to solve the expression

PEDMAS

P = parenthensis

E = exponent

D = division

M = multiplication

A = addition

S = subtraction

Step 2: Write the expression


\text{4 + (5}^2-2^3)

Step 3: Apply the PEDMAS to solve the question


\begin{gathered} 4+(5^2-2^3) \\ =\text{ 4 + (25 - 8)} \\ =\text{ 4 + 17} \\ =\text{ 21} \end{gathered}

Final answer

21

User Rolintocour
by
5.1k points